Ecological Regionalization for the Ecological Protection in Power Transmission and Transformation Projects - Mo, Hanqin; Zhao, Yanwei; Wen, Weibing; Liang, Dong; Hong, Qian (Journal of Environmental Accounting and Management, 2026)
Ecological regionalization in China is of great significance for guiding rational landscape planning and regionally differentiated ecological protection, as well as the management and layout of power transmission and transformation projects. Based on the principle of genesis, 11 indices, including elevation, slope, precipitation, river system, vegetation type, vegetation coverage, soil type, land use pattern, soil erosion intensity, bird migration pathway, and bird habitat distribution, were selected to characterize the topography, hydrology, vegetation, soil, and bird activities. Fuzzy Cmeans (FCM) cluster analysis was used to divide the country into 4 main ecoregions and 17 sub-ecoregions, and the ecological characteristics, sensitivities, and ecological protection points of each ecoregion were defined. The results show that the regionalization results is objective and feasible and can provide an operational basis for incorporating ecological planning and differentiated, large-scale ecological management into power development.